PENGARUH ARUS KAS OPERASI, ARUS KAS INVESTASI, DAN ARUS KAS PENDANAAN TERHADAP HARGA SAHAM - Desi Sulistyawati, 15.05.52.0116; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2019)
This research aims to examine and analyze the influence of operating cash flows, investment cash flows, and financing cash flows on the company stock prices againts the BUMN listed on the Indonesia Stock Exchange for the period 2013-2017. The sampling technique in this research used a saturated sampling technique. The data used is secondary data obtained from the Indonesia Stock Exchange. Metodh data analysis that are used in this research is the analysis of Multiple Linear Regression and assisted by the SPSS version 22 statistical test. The results of this study indicate that the Operating Cash Flow has a positive and not significantly effect on the Stock Price. Investment Cash Flow has a negative and not significantly effect on the Stock Price. Financing Cash Flow has a positive and significantly effect on the Stock Price.